Intellectual Property Rights Protection For Traditional Cultural Expressions - Faliani Zaliaokta; Siti Maharani; Ikhwan Aulia Fatahillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the adequacy of intellectual property protection for Traditional Cultural Expressions within Indonesia through a non empirical normative legal research design. It analyzes statutory provisions, doctrinal scholarship, and international frameworks to evaluate whether existing mechanisms sufficiently safeguard communal cultural rights. The findings indicate persistent structural misalignment between communal ownership systems and conventional copyright principles, particularly regarding authorship and originality requirements. The study further identifies weaknesses in benefit sharing arrangements, fragmented cultural documentation, and limited enforcement capacity in cross border contexts. Additionally, the emergence of artificial intelligence and generative digital technologies introduces new legal uncertainties concerning reproduction and cultural appropriation. The analysis highlights that current regulatory instruments do not adequately address these multidimensional challenges. It argues for a more integrated legal approach that combines statutory reform with conceptual reorientation toward community based governance. The study concludes that a sui generis framework is essential to ensure equitable protection, cultural sustainability, and legal certainty for Traditional Cultural Expressions in the evolving digital era.